2022
DOI: 10.1093/gji/ggac454
|View full text |Cite
|
Sign up to set email alerts
|

Cross-hole electrical resistivity tomography as an aid in monitoring marine gas hydrate reservoirs for gas recovery: an experimental simulation study

Abstract: Summary The in-situ reservoir status monitoring plays a critical role in natural gas hydrate resource production. Considering the complexity of the field environment, a simulation framework for monitoring gas hydrates with cross-hole electrical resistivity tomography (CHERT) was developed to monitor the hydrate distribution during hydrate formation and dissociation. The simulation study comprised both numerical and physical experiments. The optimal CHERT array was designed through a numerical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…They found that the formation position and heterogeneity of hydrate are controlled by the distribution of pore water and methane gas [30]. Liu et al developed a cross-borehole electrical resistivity tomography array to monitor the dynamic evolution of hydrate-bearing sediments [31]. However, most of these researches are aimed at pore-filling hydrate, and the application of ERT in fracture-filling hydrate has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the formation position and heterogeneity of hydrate are controlled by the distribution of pore water and methane gas [30]. Liu et al developed a cross-borehole electrical resistivity tomography array to monitor the dynamic evolution of hydrate-bearing sediments [31]. However, most of these researches are aimed at pore-filling hydrate, and the application of ERT in fracture-filling hydrate has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%